EL REALISMO SOCIALISTA EN EL DEBATE CULTURAL CUBANO DE LA DÉCADA DE 1970 - González Yera , Madonna (Cultura Latinoamericana, 2022)
The Cuban revolution, in its process of symbolic formation, is articulated in a synthesis of the codes from the international socialist movement, concentrated in the USSR, with the elements of the national culture. The use of ideological resources such as art, brought with it the discussion about how the revolutionary artistic production should be oriented from its beginnings. The approach to the USSR starting in the 1970s and the importation of mechanisms of social organization from it, placed socialist realism, as an official method of creation, in the discussion about art. Cuban intellectuals of the decade developed positions in defense or criticism of socialist realism as part of Cuban cultural policy. Being approached in an implicit way in the treatment of art and culture in the revolution. The present work exposes some of the essential moments of the context of elaboration of the Cuban position regarding socialist realism. A position that has not been fully studied, but from which the general lines and the main figures of the Cuban intelligentsia who addressed ideas on the subject are established.